Act now: protect our present, secure our future: the academia - Muda, Mohd Rahimi; Dali, Ahmad Fauzi (Faculty of Pharmacy, 2025)
From 19 to 21 September 2025, our academic staffs from the Department of Pharmacy Practice and Clinical Pharmacy, Mr. Mohd Rahimi Muda and Mr. Ahmad Fauzi Dali, attended the Population Approach Group of Australia and New Zealand (PAGANZ) Scientific Meeting and Workshop at Bioinformatic Institute A*STAR, Singapore. This international event serves as a key platform for researchers to share and discuss advances in population modelling and simulation within pharmacometrics.